(untitled) (Conferencea, 2023)
In our systems software of supply more and more increased going role account received without , last one how many ten in annuals " software supply about quality " . worry constant respectively grow up went , this basically another factors with one in line reliability with is described .Software of supply reliability is known one in the environment known time during computer of the program fault free performance probability _ Software of supply not working stay for many reasons available , but usually they are new or changed requirements , re seeing exits or corrections and etc as a result surface coming design problems with depend There is problems if , har always failures _ immediately do not create , then they are only known circumstances and in inputs to work falls _ Reliability operational efficiency point of view in terms of is determined , the product ready to be until him measure possible not _ Reliability indicators provide for system from completion before to reliability effect doer a model is created from the factors and from him after system work outgoing at the time his concept based on his predictions is constructed ([1], [4]).Prophecy to do system unknown parameters determination and the results comment for prophecy to do procedures collection with together mathematician from the model consists of ([1], [2], [3], [4]).